2005
DOI: 10.1007/s00467-005-1852-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal pregnancy vomiting and offspring salt taste sensitivity and blood pressure

Abstract: The purpose of this study was to investigate the relationship between salt taste perception and blood pressure (BP) in normotensive adolescents as modified by maternal fluid losses during the first trimester of gestation. Seventy-two healthy adolescents (42 boys) aged between 9.0-21.1 years, recruited from the population-based RICARDIN study, were included. A maternal questionnaire about the duration of pregnancy, birth weight and vomiting or diarrhoea in the first trimester of gestation was collected. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…However, it is worth noting that high-Na diets were fed to adult animals in these studies ( 23 , 50 ) , which differs from the protocol used in the present study. Another study has demonstrated that mothers who have suffered episodes of vomiting and dehydration during the first 3 months of pregnancy give birth to children who have increased systolic pressure during adolescence ( 51 ) . Vidonho et al ( 24 ) found offspring born to mothers fed a high-Na diet (4 or 8 % NaCl) during pregnancy and lactation to have higher arterial pressure in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that high-Na diets were fed to adult animals in these studies ( 23 , 50 ) , which differs from the protocol used in the present study. Another study has demonstrated that mothers who have suffered episodes of vomiting and dehydration during the first 3 months of pregnancy give birth to children who have increased systolic pressure during adolescence ( 51 ) . Vidonho et al ( 24 ) found offspring born to mothers fed a high-Na diet (4 or 8 % NaCl) during pregnancy and lactation to have higher arterial pressure in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship to NLS remains to be clarified, since we show here that sodium consumption at 8 to 15 yr is better explained by NLS than birth weight. The contribution of maternal vomiting needs to be considered too, since it relates to both reduced birth weight (54), to increased sodium appetite in the offspring (9,10,27), and to NaCl gustatory thresholds and blood pressure in adolescents (32).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recognized that sodium depletion enlists the renin-angiotensin-aldosterone system, primarily central but also peripheral, to increase sodium intake, and the same system may also program the long-term increase in sodium appetite (12,22,31,40,41,50), even if activated in utero (4,16,27,48). It has been proposed that such perinatal alterations may be adaptive, specifically in increasing sodium appetite (12,14,23,29) or, more generally, to meet cardiovascular and hydrational challenges, occasionally referred to as "programming" or "imprinting" (3,5,6,32,38).…”
Section: Discussionmentioning
confidence: 99%
“…A lavagem da boca com água entre as soluções com diferentes concentrações de NaCl foi realizada em 77,3% (n = 17) dos artigos e, em cinco, não consta a informação (ELLEGARD et al, 2007a;SIENKIEWICZ-JAROSZ et al, 2005;MALAGA et al, 2003MALAGA et al, , 2005UKOH et al, 2004). Pode haver a diluição do NaCl na saliva após degustação do estímulo, com comprometimento da próxima avaliação, e lavar a boca com água minimizaria esse efeito (STONE;SIDEL, 2004;MEILGAARD et al, 1999).…”
Section: Aspectos Gerais Dos Artigos Para Avaliação Sensorialunclassified